Post-Ottoman Belgrade’s gardens as an element of own tradition in Serbian discourses of the first half of the 20th century - Sylwia Nowak-Bajcar (Porównania, 2024)
In the article are presented traces of the absence/presence of Turkish gardens and ways of their functionalization in discourses devoted to the Belgrade urban space of the first half of the 20th century, when the modern face of the city was being shaped after many centuries of Turkish slavery. In the context of identifying the post-Turkish heritage with backwardness and primitivism, it is particularly surprising that the authors of the concept of healing the urban space of Belgrade assigned the post-Turkish home gardens, which were included in the discourse of the native tradition, became the starting point for the World War II projects to adapt Ebenezer Howard’s concept of a garden city in Belgrade. This concept obviously had its aesthetic, social and economic potential, and the impossibility of its full implementation, caused by the outbreak of the First World War, meant that it did not lose its validity also in the interwar period.